Comparison of the safety profile of tofacitinib and etanercept in rheumatoid arthritis patients aged 60 years and over: The real-life data from the HUR-BIO registry - Sarıyıldız, Emine; Ünaldı, Erdinç; Kılıç, Levent; Karadağ, Ömer; Kalyoncu, Umut; Ertenli, Ali İhsan and Kiraz, Sedat (Acta Medica, 2024)
Objective: To investigate the safety profile of tofacitinib in rheumatoid arthritis (RA) patients aged 60 and over and to compare these findings with etanercept. Materials and methods: HUR-BIO (Hacettepe University Rheumatology Biologic Registry) is a single-center registry for biological and targeted synthetic DMARDs since 2005. We included RA patients aged ≥ 60 years who were prescribed tofacitinib or etanercept as their first bDMARD or tsDMARD and had at least one control visit. MACE (major adverse cardiovascular event), VTE (venous thromboembolism), malignancy, herpes zoster, and infections requiring hospitalization were recorded for the safety profile. Incidence rate (IR) and incidence rate ratios (IRR) per 1000 patient years were calculated for all safety data. Results: This study consisted of 123 RA patients (tofacitinib n=70, etanercept n=53). In the overall population, the mean age was 67.9 ± 6.2 years and the median follow-up period was 2.1 years. Among the traditional cardiovascular risk factors, smoking history and hyperlipidemia were more common in the tofacitinib group. The IRR per 1000 patients years for MACE, herpes zoster, and infections requiring hospitalization was similar between the groups. All three patients who diagnosed with DVT or PE were in the tofacitinib group, and the significance level of the increase in IR was close to the statistical threshold (p=0.057). There was only one patient who developed non-melanoma skin cancer, and that patient was in the tofacitinib group. Conclusion: The incidence of MACE, herpes zoster, and infections requiring hospitalization was comparable between tofacitinib and etanercept. However, the occurrence of VTE exclusively in the tofacitinib group suggests that this issue needs careful evaluation for these patients.